ER/K linked GPCR-G protein fusions systematically modulate second messenger response in cells - Rabia U. Malik (Nature Portfolio, 2017)
Abstract FRET and BRET approaches are well established for detecting ligand induced GPCR-G protein interactions in cells. Currently, FRET/BRET assays rely on co-expression of GPCR and G protein, and hence depend on the stoichiometry and expression levels of the donor and acceptor probes. On the other hand, GPCR-G protein fusions have been used extensively to understand the selectivity of GPCR signaling pathways. However, the signaling properties of fusion proteins are not consistent across GPCRs. In this study, we describe and characterize novel sensors based on the Systematic Protein Affinity Strength Modulation (SPASM) technique. Sensors consist of a GPCR and G protein tethered by an ER/K linker flanked by FRET probes. SPASM sensors are tested for the β2-, α1-, and α2- adrenergic receptors, and adenosine type 1 receptor (A1R), tethered to Gαs-XL, Gαi2, or Gαq subunits. Agonist stimulation of β2-AR and α2-AR increases FRET signal comparable to co-expressed FRET/BRET sensors. SPASM sensors also retain signaling through the endogenous G protein milieu. Importantly, ER/K linker length systematically tunes the GPCR-G protein interaction, with consequent modulation of second messenger signaling for cognate interactions. SPASM GPCR sensors serve the dual purpose of detecting agonist-induced changes in GPCR-G protein interactions, and linking these changes to downstream signaling.